Technology and College Student Mental Health: Challenges and Opportunities - Lattie, Emily G.; Lipson, Sarah Ketchen; Eisenberg, Daniel (Frontiers in Psychiatry, 2019)
In recent years, there has been an increase in symptoms of depression, anxiety, eating disorders, and other mental illnesses in college student populations. Simultaneously, there has been a steady rise in the demand for counseling services. These trends have been viewed by some as a mental health crisis requiring prompt investigation and the generation of potential solutions to serve the needs of students. Subsequently, several studies linked the observed rise in symptoms with the ubiquitous rise in use of personal computing technologies, including social media, and have suggested that time spent on these types of technologies is directly correlated with poor mental health. While use of personal computing technologies has dramatically shifted the landscape in which college students connect with one another and appears to have some detriments to mental health, the same technologies also offer a number of opportunities for the enhancement of mental health and the treatment of mental illness. Here, we describe the challenges and opportunities for college student mental health afforded by personal computing technologies. We highlight opportunities for new research in this area and possibilities for individuals and organizations to engage with these technologies in a more helpful and wellness-promoting manner.